Hubungan Obesitas Terhadap Kualitas Hidup Remaja Di SMA Santo Paulus Pontianak - Ramadhaniyati Ramadhaniyati; Uji Kawuryan; Bonifasia Ermiyati Sundaria (Jurnal Keperawatan dan Kesehatan, 2015)
Obesity is a condition that occurs as a result of food consumption that far exceeds demand. Obesity in Indonesia continues to increase both in urban and rural areas . Obesity can increase the risk of morbidity and mortality and causes of delay in physical function and psychological impact on the quality hidup.Tujuan study is to examine the relationship between obesity and quality of life of adolescents . This study used a cross sectional design. The sample was all over St. Paul high school students who meet the criteria Pontianak, to get the data obesity anthropometric measurements of height and weight . Quality of life data were collected through questionnaires . Univarian data analysis using frequency distribution, bivarian using independent t test . Then from the results of the data processing can determine the relationship between adolescent obesity on quality of life in St. Paul high school Pontianak.